Power point: developing writing skills of young learners with different learning styles - a case study - Radzita bt Radzi (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
Early learning experience is suggested as one of the contributing factors to writing blocks at a later stage among learners. In finding out ways of instruction that best correspond to learners' learning style, technological aids have offered a range of effective tools helping to avert such negative development. The relationship between learners' learning style and their writing performance when Power Point is used, is examined in this work. This paper looks at the possibility of encouraging learners with visual, auditory, kinesthetic and tactile learning styles to develop their writing skills by using Power Point. A case study was conducted on the writing performance of 34 primary school students of a national type Malaysian government school, with the expectation of establishing a correlation between their learning style and writing performance. Data collection inventory consisted of (a) a questionnaire, (b) observations, (c) interviews, and (d) essay rating. Data were synchronized and analyzed using SPSS. The analysis revealed no significant correlation between learners' learning style and writing performance when Power Point was used as a teaching aid. The findings also revealed that visual learners did not perform better than those with other learning styles when Power Point was used.